2021
DOI: 10.21608/asnj.2022.106384.1266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lukewarm water compresses versus cold gel packs on breast engorgement among puerperal women

Abstract: Breast engorgement can cause breastfeeding difficulties. Different non-pharmacological methods to relieve breast engorgement have been attempted and investigated. The aim of the study was to assess the effect of lukewarm water compresses versus cold gel packs on breast engorgement among puerperal women. Subject and method: A quasi-experimental research design was utilized. This study was conducted at the Obstetric and Gynecologic Department of Damanhur National Medical Institution at El-Behira Governorate. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Additionally, supporting the findings of the current investigation, Lamadah et al’s [ 8 ] findings showed no statistically significant differences between the two groups before and after the first intervention day. After the second intervention day, a highly statistically significant difference (P = 0.000) was found.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Additionally, supporting the findings of the current investigation, Lamadah et al’s [ 8 ] findings showed no statistically significant differences between the two groups before and after the first intervention day. After the second intervention day, a highly statistically significant difference (P = 0.000) was found.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of Kumari [ 2 ], which supported the findings of the current study, showed that there were no statistically significant differences between the experimental and control groups in terms of sociodemographic and obstetric data. Additionally, the results of Lamadah et al [ 8 ] showed that the mean age of the group receiving lukewarm water compresses was approximately 23 years and four months and that of the group receiving cold gel packs was approximately 25 years and six months. A total of 90% and 92.5%, respectively, of participants in both categories were homemakers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations